Digital public relations and its role in prioritizing the masses: An analytical study of the United Nations website : (A paper extracted from a PhD dissertation) - Al-asady, Laith Abdullatif; Al-azzawi, Salim Jassem (ALBAHITH ALALAMI, 2022)
This paper aims to identify how the United Nations works through its website in prioritizing audiences towards international issues، by identifying the digital PR mechanisms used in digital PR contents in prioritizing audiences towards the international issues they deal with. To achieve the objectives of this paper, the researcher used the survey method and content analysis tool with a view to identifying the ranking of international issues on the website of health، peace and security، humanitarian assistance، human rights، women، migrants، refugees and displaced persons، economic development، United Nations affairs، culture and education، environment and climate، sustainable development, and law and crime prevention. One of the most important findings the researcher reaches at is the attempt by the United Nations، through its communication contents to prioritize audiences towards international issues by highlighting important international issues of lesser concern. Thus, in order to prioritize audiences towards these issues، the United Nations has tried through digital video to prioritize audiences towards international issues which has important advantages of having the element of movement that the audience feels at the heart of the event; this brings to the fore important international issues of lesser concern. Thus, prioritizing the public towards these issues.